2008
DOI: 10.1063/1.2891787
|View full text |Cite
|
Sign up to set email alerts
|

Plasma damage mechanisms for low-k porous SiOCH films due to radiation, radicals, and ions in the plasma etching process

Abstract: Low dielectric constant (low-k) films have been widely used as insulating materials in ultra-large-scale integrated circuits. Low-k films receive heavy damage during the plasma processes of etching or ashing, resulting in an increase in their dielectric constant. In order to realize damage-free plasma processes for low-k films, it is essential to determine the influence of radiation, radicals, and ions emitted in the plasma process on the characteristics of low-k films. We have developed a technique to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
94
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 136 publications
(94 citation statements)
references
References 13 publications
(12 reference statements)
0
94
0
Order By: Relevance
“…5) In the case of the plasma-induced physical damage (PPD), it creates local defect structures in materials such as vacancies and interstitials. These damage structures are considered to behave as carrier-trapping sites, thus, result in the changes in the dielectric constant ε and the capacitance C. Regarding the PID to dielectric materials, the previous studies showed that the PID to "low-k" films -interlayer dielectric materials -led to changes in ε 6,7) and C. 8,9) Shinohara et al investigated 10) the time evolution of leakage current flowing through dielectric materials under constant voltage stressing for the evaluation of PID in thick SiO 2 films. They found that the initial electron trapping rate depends on the amount of PID.…”
Section: Introductionmentioning
confidence: 99%
“…5) In the case of the plasma-induced physical damage (PPD), it creates local defect structures in materials such as vacancies and interstitials. These damage structures are considered to behave as carrier-trapping sites, thus, result in the changes in the dielectric constant ε and the capacitance C. Regarding the PID to dielectric materials, the previous studies showed that the PID to "low-k" films -interlayer dielectric materials -led to changes in ε 6,7) and C. 8,9) Shinohara et al investigated 10) the time evolution of leakage current flowing through dielectric materials under constant voltage stressing for the evaluation of PID in thick SiO 2 films. They found that the initial electron trapping rate depends on the amount of PID.…”
Section: Introductionmentioning
confidence: 99%
“…During plasma etching and ashing processes, carbon depletion, surface hydrophilisation, and surface densification have been observed, increasing the effective dielectric constant and leakage current [3][4][5][6][7][8][9][10][11]. These plasma damages limit the further scaling of low-k structures and have stimulated considerable interests in the study of dielectric recovery by silyation methods, using vapor-phase [12], liquidphase [13][14], and supercritical CO 2 processes [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…As with electrical charge-up and ion bombardment, photons in the UV and especially in the vacuum ultraviolet (VUV) regions emitted from plasma also induce damage on device materials [9][10][11][12][13][14][15][16][17]. Although the number of reports on UV-induced damage in LSI fabrication is much smaller than those on damage induced by electrical charge-up and ion bombardment, the recent increase in the use of organic materials in electronic devices, e.g., for low-k dielectric barrier and flexible semiconductors, has highlighted the ever-growing importance of the study on UV-induced damage in plasma processing.…”
Section: Introductionmentioning
confidence: 99%